Of hissing snakes and angry voices: human infants are differentially responsive to evolutionary fear-relevant sounds - Erlich, N.; Lipp, Ottmar; Slaughter, V. (Blackwell Publishing Ltd, 2013)
Adult humans demonstrate differential processing of stimuli that were recurrent threats to safety and survival throughout evolutionary history. Recent studies suggest that differential processing of evolutionarily ancient threats occurs in human infants, leading to the proposal of an inborn mechanism for rapid identification of, and response to, evolutionary fear-relevant stimuli. The current study provides novel data in support of this proposal, showing for the first time that human infants differentially process evolutionary threats presented in the auditory modality. Sixty-one 9-month-olds listened to evolutionary fear-relevant, modern fear-relevant, and pleasant sounds, while their heart rate, startle, and visual orienting behaviours were measured. Infants demonstrated significantly enhanced heart rate deceleration, larger eye-blinks, and more visual orienting when listening to evolutionary fear-relevant sounds compared to sounds from the other two categories. These results support the proposal that human infants possess evolved mechanisms for the differential processing of a range of ancient environmental threats.